Ester Hydrolysis Differentially Reduces Aconitine-Induced Anti-hypersensitivity and Acute Neurotoxicity: Involvement of Spinal Microglial Dynorphin Expression and Implications for Aconitum Processing - Li, Teng-Fei; Gong, Nian; Wang, Yong-Xiang (Frontiers in Pharmacology, 2016)
Aconitines, including bulleyaconitine A, probably the most bioactive and abundant alkaloids in Aconitum plant, are a group of diester C19-diterpenoid alkaloids with one acetylester group attached to C8 of the diterpenoid skeleton and one benzoylester group to C14. Hydrolysis of both groups is involved in the processing of Aconitum, a traditional Chinese medicinal approach. We recently demonstrated that bulleyaconitine A produced anti-hypersensitivity, which was mediated by stimulation of spinal microglial dynorphin A expression. This study aimed to elucidate whether the acetylester and benzoylester groups are involved in aconitine-induced dynorphin A expression, anti-hypersensitivity, neurotoxicity in neuropathic rats. Intrathecal administration of aconitine and benzoylaconine (but not aconine) attenuated mechanical allodynia and heat hyperalgesia, with normalized ED50 values of 35 pmol and 3.6 nmol, respectively. Aconitine and benzoylaconine anti-allodynia was completely blocked by the microglial inhibitor, dynorphin A antiserum, and κ-opioid receptor antagonist. Aconitine and benzoylaconine, but not aconine, stimulated dynorphin A expression in cultured primary spinal microglia, with EC50 values of 32 nM and 3 μM, respectively. Intrathecal aconitine, benzoylaconine and aconine induced flaccid paralysis and death, with normalized TD50 values of 0.5 nmol, 0.2 μmol, and 1.6 μmol, respectively. The TD50/ED50 ratios of aconitine and benzolyaconine were 14:1 and 56:1. Our results suggest that both the C8-acetyl and C14-benzoyl groups are essential for aconitine to stimulate spinal microglial dynorphin A expression and subsequent anti-hypersensitivity, which can be separated from neurotoxicity, because both benzoylaconine and aconine differentially produced anti-hypersensitivity and neurotoxicity due to their different stimulatory ability on dynorphin A expression. Our results support the scientific rationale for Aconitum processing, but caution should be taken to avoid overprocessing and excess hydrolysis of benzolyaconine to aconine.